2005
DOI: 10.1111/j.1538-7836.2005.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin-converting enzyme insertion/deletion and plasminogen activator inhibitor-1 4G/5G gene polymorphisms in retinal vein occlusion

Abstract: Retinal vein occlusion (RVO) is one of the leading causes for a severe visual loss in patients older than 60 years. Hypofibrinolysis because of increased plasminogen activator inhibitor-1 (PAI-1) plasma concentrations has been identified as a risk factor [1][2][3]. Yet only very limited and at least partly conflicting data on the role of gene polymorphism known to affect PAI-1 plasma levels are available [2][3][4]. Recently, Gori et al. [2] investigating 112 patients with RVO suggested both homozygosity for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
1
1
Order By: Relevance
“…In addition Glueck et al [14] demonstrated that factor V mutation, high levels of heritable factor VIII, high homocysteine levels and low levels of antithrombin III are associated with CRVO as a familial thrombophlia. There were studies reporting findings those are opposite to our study results [30]. Furthermore in a recent study an association among RVO and ACE gen polymorphism was not demonstrated [31].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition Glueck et al [14] demonstrated that factor V mutation, high levels of heritable factor VIII, high homocysteine levels and low levels of antithrombin III are associated with CRVO as a familial thrombophlia. There were studies reporting findings those are opposite to our study results [30]. Furthermore in a recent study an association among RVO and ACE gen polymorphism was not demonstrated [31].…”
Section: Discussioncontrasting
confidence: 99%
“…PAI-1 activity was determined by the PAI-1 4G/5G polymorphism by polymerase chain reaction and restriction length fragment polymorphism. In another study, Mattes et al [ 12 ] found that among all patients with RVO, 54.5% had the PAI-1 4G/5G gene polymorphism. Conversely, for the angiotensin-converting enzyme (ins/del) and PAI-1 (4G/5G) mutations, no difference was observed between the genotypes of patients with RVO and those of control participants in the study by Russo et al [ 13 ] and Kuhli-Hattenbach et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gori ve arkadaş-ları, RVT olan hastalarda homozigotik anjiotensin konverting enzim (AKE) insersiyon/delesyon için, (PAI-1 4G/4G ve AKE DD) genotiplerinin bir risk faktörü olduğunu ileri sürmüşlerdir [18]. Ancak Mattes ve arkadaşları ise AKE DD genotipini RVT olan hastalarda önceki yayınla tersi şekilde yüksek bulamamışlar [19]. Trombofilik, gen polimorfizmleri ve RVDT riskini araştıran çalış-mada; faktör V R506Q (faktör V Leiden), protrombin 20210G>A, fibrinojen beta -455G> A, faktör XII (FXII) 46C>T, ve ITGA2 807C>T (platelet glikoprotein Ia [GPIa] 807C>T) ve ITGB3 L59P (platelet GPIIIa PlA1/PlA2) polimorfizmleri çalışılmış ve bu ça-lışma sonunda RVDT olan hastalar ve kontrol grubu arasında risk açısından fark bulamamışlardır [15].…”
Section: Discussionunclassified